Antimicrobial resistance among commensal Escherichia coli from cattle faeces and beef in Ibadan, Nigeria (2012)
Commensal bacteria contribute to the distribution and persistence of antimicrobial resistance in the environment. This study monitored antimicrobial resistance in commensal Escherichia coli from the faeces of on-farm and slaughter cattle and beef. A total of 342 (89.5%) E. coli isolates were obtained from 382 samples. Isolation rate of E. coli was 90.0% in on-farm cattle, 87.1% in slaughter cattle and 92.2% in beef. Overall, the isolates showed resistance to amoxicillin (97.9%), ampicillin (97.9%), cefuroxime (25.1%), chloramphenicol (69.3%), ciprofloxacin (11.7%), cotrimazole (45.9%), erythromycin (59.4%), gentamycin (36.5%), nalidixic acid (27.2%), nitrofuratoin (54.9%), norfloxacin (21.1%), ofloxacin (14.0%), streptomycin (78.9%) and tetracycline (33.9%). There were no significant differences in antimicrobial resistance of E. coli from the different sample types. Only four (1.2%) of the 342 isolates were susceptible to all antimicrobial agents, while 338 (98.8%) were resistant to at least one of the tested antimicrobial agents. Multi-drug resistance to three or more antimicrobials was observed in 321 (93.9%) of all the isolates. Forty-one resistance groups were observed in on-farm cattle, 30 in slaughter cattle and 34 in beef. All the 30 resistance groups found in slaughter cattle were also present in on-farm cattle and beef. ‘AmoAmpChlEryNitStr’ and ‘AmoAmpChlStr’ were the predominant resistant patterns. This study confirmed on-farm and slaughter cattle as important sources of antimicrobial resistant E. coli transmissible to humans through beef.